Primary total hip arthroplasty for a femoral neck fracture in a homolateral above-knee amputee: a case report - Xu, Changli; Yin, Yu; Shi, Hongchen; Li, Zhengqiang; Qiao, Suchi; Bu, Jianli (Frontiers in Surgery, 2026)
IntroductionFemoral neck fracture in a homolateral amputated extremity is not common and challenging for the surgeon to manage. In this article we share our experience of this unusual entity.MethodsWe present a case of a displaced femoral neck fracture of the right femur in a 69-year-old female, who underwent at the age of 29 an above-knee amputation of the homolateral limb. The fracture was managed by a primary total hip arthroplasty (THA). The post-operative course was uneventful. There was no infection, deep vein thrombosis, dislocation, or any other complication.ResultsOver one-year follow-up demonstrated that the patient while wearing the prosthetic limb received satisfactory and functional use of normal activities. The patient achieved a good functional outcome with a Harris Hip Score at 86/100. To date, the patient has returned to normal activities without symptoms.ConclusionTreating femoral neck fractures in homolateral above-Knee amputees is challenging. Surgical technical tips and rehabilitation exercises are necessary and crucial. Total hip arthroplasty can provide satisfactory functional outcome and return to pre-fracture daily life activities.